Indexing strategy and web visibility of the Revista Cubana de Tecnología de la Salud - Araujo Inastrilla, Carlos Rafael; Llosa-Santana, Mayelin; Gutiérrez-Vera, Dayami; Cárdenas Hernández, Dalila; Manzanet-Valladares, Katherine (AWARI, 2024)
Indexing consists of recording data and information arranged in an index whose content is related to the search terms, showing a location. The algorithm used to index a scientific journal is a visible topic. It implies a need for professionals in charge of editorial management to achieve the highest quality standards. An indexing strategy was designed to contribute to the visibility and international positioning of the Revista Cubana de Tecnología de la Salud. An applied research was carried out between January 2020 and March 2023 in the Revista Cubana de Tecnología de la Salud. The strategy was developed through general scientific research methods, with the support of statistical methods, to analyze the first results. A strategy was designed to index the journal in the indexing and impact summary systems to improve its visibility and position nationally and internationally. The strategy consisted of four stages: diagnosis, planning, execution, and evaluation. Partial results demonstrate the increase in the number of indexings made by the journal.